2020
DOI: 10.2463/mrms.mp.2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <i>b</i>-Value Sampling Scheme on Brain IVIM Parameter Estimation in Healthy Subjects

Abstract: Purpose: Intravoxel incoherent motion (IVIM) analysis has attracted the interest of the clinical community due to its close relationship with microperfusion. Nevertheless, there is no clear reference protocol for its implementation; one of the questions being which b-value distribution to use. This study aimed to stress the importance of the sampling scheme and to show that an optimized b-value distribution decreases the variance associated with IVIM parameters in the brain with respect to a regular distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 46 publications
(79 reference statements)
3
34
0
1
Order By: Relevance
“…Low b values were defined as the values below 200 s/mm 2 . Values 200, 900 were fixed to follow suggestions of earlier b value set optimization studies [ 29 , 33 ], and were considered as suggested optimal for optimizing f parameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low b values were defined as the values below 200 s/mm 2 . Values 200, 900 were fixed to follow suggestions of earlier b value set optimization studies [ 29 , 33 ], and were considered as suggested optimal for optimizing f parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Lemke et al studied b value distribution in liver (Lemke et al, 2011). In the brain, Chabert et al studied 10 subjects with two b value distributions (Chabert et al, 2019). Hu et.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, many researchers have studied how to optimize the b‐values for IVIM quantification 12,19,22 . Although there have been many studies to find the optimal b‐values for a long time, there is little studies to find generalized optimal b‐values for IVIM quantification 12,18‐22,31,32 …”
Section: Methodsmentioning
confidence: 99%
“…12,19,22 Although there have been many studies to find the optimal b-values for a long time, there is little studies to find generalized optimal b-values for IVIM quantification. 12,[18][19][20][21][22]31,32 (1)…”
Section: Comparison Methodsmentioning
confidence: 99%
“…Esta é uma evidência de que a técnica IVIM, aplicada da forma como foi aqui, pode ser ineficaz na busca por um padrão de valores que caracterizem determinados tecidos cerebrais, pois estes valores variam muito conforme o sujeito analisado. Para efeitos de comparação, a tabela 3 contém exemplos extraídos da literatura 173 ; valores diferentes dos estimados e dos exemplos podem ser encontrados. 107,128,162,167,174 Para se obter os valores desta tabela, 10 pacientes foram analisados com o método IVIM e houve superestimação de f e D, em todas as áreas, em relação aos calculados com a interface desenvolvida aqui; além disso, os valores da variabilidade dos 30 pacientes são muito maiores.…”
Section: Cálculo De Snrunclassified